Functional Characterization of Class I Trehalose Biosynthesis Genes in Physcomitrella patens - Phan, Tran Le Cong Huyen Bao; Delorge, Ines; Avonce, Nelson; Van Dijck, Patrick (Frontiers in Plant Science, 2020)
The function of trehalose metabolism in plants during growth and development has been extensively studied, mostly in the eudicot Arabidopsis thaliana. So far, however, not much is known about trehalose metabolism in the moss Physcomitrella patens. Here, we show that in P. patens, two active trehalose-6-phosphate synthase enzymes exist, PpTPS1 and PpTPS2. Expression of both enzymes in Saccharomyces cerevisiae can complement the glucose-growth defect of the yeast tps1∆ mutant. Truncation of N-terminal extension in PpTPS1 and PpTPS2 resulted in higher TPS activity and high trehalose levels, upon expression in yeast. Physcomitrella knockout plants were generated and analyzed in various conditions to functionally characterize these proteins. tps1∆ and tps2∆ knockouts displayed a lower amount of caulonema filaments and were significantly reduced in size of gametophores as compared to the wild-type. These phenotypes were more pronounced in the tps1∆ tps2∆ mutant. Caulonema formation is induced by factors such as high energy and auxins. Only high amounts of supplied energy were able to induce caulonema filaments in the tps1∆ tps2∆ mutant. Furthermore, this mutant was less sensitive to auxins as NAA-induced caulonema development was arrested in the tps1∆ tps2∆ mutant. In contrast, formation of caulonema filaments is repressed by cytokinins. This effect was more severe in the tps1∆ and tps1∆ tps2∆ mutants. Our results demonstrate that PpTPS1 and PpTPS2 are essential for sensing and signaling sugars and plant hormones to monitor the balance between caulonema and chloronema development.